2023
DOI: 10.1101/2023.01.29.526148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatio-temporal evaluation of drought adaptation in wheat revealed NDVI and MTSI as powerful tools for selecting tolerant genotypes

Abstract: Context: Water stress is fast becoming a major limiting factor for wheat production. Hence, identifying drought tolerant genotypes is critical for sustaining the food supply chain. However, there are no phenotypic markers or statistical models available that may be employed for the efficient selection of field grown drought tolerant wheat genotypes. Objectives: We evaluated wheat genotypes to (1) identify novel sources of drought tolerance (2) understand underlying adaptation mechanisms of drought tolerance (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…For wheat crops, different levels of drought-tolerance mechanisms, involving changes in physiological processes of plant leaves, have been observed. Metabolic disruptions and great yield loss result from the activation of different mechanisms, including water and minerals uptake, CO 2 assimilation, transpiration, stomatal conductance, chlorophyll concentrations, stomatal density and cell wall integrity ( Hachani et al., 2022 ; Srinatha et al., 2023 ). Various study have shown differences in the capacity of plant species to perform stomatal regulation, osmotic adjustment and to change the leaf tissues elastic properties ( Martínez et al., 2007 ; Hessini et al., 2008 ; Sampaio Filho et al., 2018 ; Leuschner et al., 2019 ; Wood et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…For wheat crops, different levels of drought-tolerance mechanisms, involving changes in physiological processes of plant leaves, have been observed. Metabolic disruptions and great yield loss result from the activation of different mechanisms, including water and minerals uptake, CO 2 assimilation, transpiration, stomatal conductance, chlorophyll concentrations, stomatal density and cell wall integrity ( Hachani et al., 2022 ; Srinatha et al., 2023 ). Various study have shown differences in the capacity of plant species to perform stomatal regulation, osmotic adjustment and to change the leaf tissues elastic properties ( Martínez et al., 2007 ; Hessini et al., 2008 ; Sampaio Filho et al., 2018 ; Leuschner et al., 2019 ; Wood et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%